Pemanfaatan Buku Kesehatan Ibu dan Anak (KIA) Oleh Orang Tua Sebagai Upaya Pencegahan Kekerasan Seksual Pada Anak Usia Dini: Studi Kualitatif - Hafsah; Himatul Khoeroh (Bunda Edu-Midwifery Journal (BEMJ), 2025)
Sexual violence against young children has become one of the major issues that continues to occur throughout Indonesia. The issue of sexual violence against young children can have a significant impact both physically and mentally on the child. Cases of sexual violence require special attention from both the family environment and the community environment. One effective way to prevent sexual violence against young children is to take a comprehensive approach with parents by utilizing the mother and child health book (MCH) as an educational medium. The use of the maternal and child health book (MCH) by parents can enhance their knowledge about the efforts needed to prevent sexual violence against young children. The research method used was qualitative with interview techniques on 5 participants. The research findings indicate that not all parents understand the MCH book, so its use is limited to being a tool for monitoring children's health. The conclusion of the research obtained is that not all parents can utilize the MCH book as an information medium to prevent sexual violence in early childhood.